Innovation in Teacher Education: A QR-Code Integrated Textbook for Developing Personality and Teaching Competence - Pratiwi, Vivi; Panduwinata, Lifa Farida; Saputra, Irwan Adimas Ganda; Listiadi, Agung; Hakim, Luqman; Cahya, Septyan Budy; Husna, Netty Elliya (International Journal of Studies in International Education, 2025)
The study aims to produce a textbook called Basic Teaching and Learning Skills in the Aspect of Teacher Personality Competence Integrated with QR-Code to improve the quality of professional teacher competence. The study applied the Research and Development (R&D) methodology based on the ADDIE model. The findings indicated that there was high level of feasibility, including material expert validation 83.3, language validation 88.3 and student responses 95.5 which is categorized as very feasible. The results show that the implementation of the QR-Code can increase the level of interactivity to watch the videos, case studies, reflective materials that reinforce the level of conceptual knowledge and internalization of the characters. The findings synthesis is in accordance with Technological Pedagogical Content Knowledge (TPACK) and experiential learning theories, and technology is the reflective medium in personality development. It concludes that the QR-Code textbook is a productive, innovative, and topical medium to form teacher personality competence, which is consistent with the curriculum and the demand of transformation education digital. The product will help improve innovation in higher education by helping close the gap between the pedagogical content and digital literacy and providing adaptive and professional teachers to meet the demands of the 21st-century education.